Analisis Kompetensi Lulusan SMK dalam Menghadapi Dunia Kerja (Studi Kasus di Kabupaten Aceh Tamiang) - Andayani, Isniar (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
Alumni’s competence of vocational high schools (SMK) is one of the indicators needed by job market. The purpose of this study was to analyze the competence of in job market in Aceh Tamiang Regency. It applied qualitative method. In this study, the researcher was as a key instrument in collecting the data through observation, interviews, and documents. The results showed that the societies of SMK alumni who have got the job was 8.01 percent and was far behind from SMA/MA/Package C alumni, which was 24.88 percent. In response to this, it is necessary to align the curriculum with the needs of the job market so that there is synergy and cooperation between SMK, the business world, and the industrial world. A discussion of the curriculum can involve the government, the private sector, schools, and teachers, LSM, academics, and other related parties. Curriculum development must be based on the characteristics, needs, and regional developments such as regional long and medium development plans.